An Emergent Framework of the Market Food Environment in Low- and Middle-Income Countries. Issue 4 (13th March 2021) - Toure, Djeinam; Herforth, Anna; Pelto, Gretel H; Neufeld, Lynnette M; Mbuya, Mduduzi N N
ABSTRACT: Background: Food systems are increasingly recognized as critical for advancing nutrition, and the food environment is viewed as the nexus between those systems and dietary consumption. Developing a measurement framework of the market food environment is a research priority, particularly for low- and middle-income countries (LMICs), which face rapid shifts in markets, dietary patterns, and nutrition outcomes. Objectives: In this study, we sought to assess current conceptions and measures of the market food environment that could be adapted for use in LMICs. Methods: We conducted a narrative review of the literature to identify measures of the market food environment in recent use. First, we identified and reviewed frameworks of the food environment for LMICs with a specific focus on the market food environment. Second, we compiled 141 unique measures of the market food environment from 20 articles into a list that was pile-sorted by 5 nutrition experts into domains. We then categorized the measures based on percentage agreement across all sorts. Finally, we compared measured and conceptual domains of the market food environment to identify measurement gaps and needed adaptations. Results: Conceptual frameworks provide differing definitions of the market food environment but conform in their definitions of food availability, price, marketing, and product characteristics. Greater clarity is needed in defining relevant vendor and product characteristics. Eight measured domains of the market food environment emerged from the literature review, with significant overlap among conceptual domains. Measurement gaps exist for food quality, safety, packaging, desirability, and convenience. Personal characteristics also emerged as measured domains, although these are not part of the food environment per se. Conclusions: These results are a step toward elucidating how, why, and where we measure the market food environment in LMICs. Future research should focus on prioritizing the most meaningful methods and metrics and on developing new measures where gaps exist. Abstract : The food environment is the nexus between food systems and dietary consumption. This study elucidates how, why, and where we measure the market food environment in low- and middle-income countries.